The Relationship of Long Time Hemodialization with Anxiety Level in Chronic Kidney Failure Patients - Rona Samsinar; Eli Indawati; Achmad Fauzi (STIKep PPNI Jawa Barat, 2022)
Aims: To assess the relationship between the length of hemodialysis time and the level of anxiety in patients with chronic kidney failure at the Jakarta Harbor Hospital in 2021 Design: Analytical with cross sectional. Methods: The data used is primary data, namely data obtained from the results of distributing questionnaires. The data collection instrument used was a questionnaire. The analytical method used was univariate analysis and bivariate analysis with Chi Square test. Results: The majority of respondents with mild anxiety and undergoing hemodialysis > 24 months. There is a relationship between the length of hemodialysis time and the level of anxiety in CKD patients with p value < 0.05 Conclusions: There is a relationship between the length of time on hemodialysis and the level of anxiety in CKD patients. Therefore, clinical nurse needs to provide an important intervention or pleasant activity during the patients undergoing hemodialysis to reduce level of anxiety.